Dyadic Interference Leads to Area of Uncertainty During Face-to-Face Cooperative Interception Task - Faure, Charles; Limballe, Annabelle; Sorel, Anthony; Perrin, Théo; Bideau, Benoit; Kulpa, Richard (Frontiers in ICT, 2019)
People generally coordinate their action to be more efficient. However, in some cases, interference between them occur, resulting in an inefficient collaboration. For example, if two volleyball players collide while performing a serve reception, they can both miss the ball. The main goal of this study is to explore the way two persons regulate their actions when performing a cooperative task of ball interception, and how interference between them may occur. Starting face to face, twenty-four participants (twelve teams of two) had to physically intercept balls moving down from the roof to the floor of a virtual room. To this end, they controlled a virtual paddle attached to their hand moving along the anterior-posterior axis. No communication was allowed between participants so they had to focus on visual cues to decide if they should perform the interception or leave the partner do it. Participants were immersed in a stereoscopic virtual reality setup that allows the control of the situation and the visual stimuli they perceived, such as ball trajectories and the information available on the partner's motion. Results globally showed participants were often able to intercept balls without collision by dividing the interception space in two equivalent parts. However, an area of uncertainty (where many trials were not intercepted) appeared in the center of the scene, highlighting the presence of interference between participants. The width of this area increased when the situation became more complex (facing a real partner and not a stationary one) and when less information was available (only the paddle and not the partner's avatar). Moreover, participants initiated their interception later when real partner was present and often interpreted balls starting above them as balls they should intercept, even when these balls were in fine intercepted by their partner. Overall, results showed that team coordination here emerges from between-participants interactions and that interference between them depends on task complexity (uncertainty on partner's action and visual information available)